2016
DOI: 10.1371/journal.pone.0148196
|View full text |Cite
|
Sign up to set email alerts
|

Adult Asylum Seekers from the Middle East Including Syria in Central Europe: What Are Their Health Care Problems?

Abstract: BackgroundForced displacement related to persecution and violent conflict has reached a new peak in recent years. The primary aim of this study is to provide an initial overview of the acute and chronic health care problems of asylum seekers from the Middle East, with special emphasis on asylum seekers from Syria.MethodsOur retrospective data analysis comprised adult patients presenting to our emergency department between 01.11.2011 and 30.06.2014 with the official resident status of an “asylum seeker” or “ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 24 publications
5
61
1
3
Order By: Relevance
“…The preponderance of respiratory infections is consistent with recent studies in Belgium, Germany, and Switzerland [8, 15, 16]. More frequent respiratory diagnoses among new arrivals are likely attributable to conditions in Dresden’s reception centers, which often had open sleeping arrangements and minimal temperature control.…”
Section: Discussionsupporting
confidence: 84%
“…The preponderance of respiratory infections is consistent with recent studies in Belgium, Germany, and Switzerland [8, 15, 16]. More frequent respiratory diagnoses among new arrivals are likely attributable to conditions in Dresden’s reception centers, which often had open sleeping arrangements and minimal temperature control.…”
Section: Discussionsupporting
confidence: 84%
“…Taken together, refugees treated at our ICU presented with infections similar to the host population (pneumonia and urinary tract infections), which is in line with the current literature [14,36].…”
Section: Experiences From a Medical Intensive Care Unit At A Universisupporting
confidence: 89%
“…The most common health problems may be related to problems in their home countries and the journey, representing a variety of diseases including accidental injuries, gynecological and obstetric complications, dermatological diseases, cardiovascular events, gastrointestinal and respiratory problems, and mental illness [10,11]. Available evidence underlines that infectious diseases are not a health priority at first arrival [12][13][14]. A very recent work from Germany assessed the health status of 214 asylum seekers, and the main health problem was psychological illness while the prevalence of infectious and chronic diseases was low [15].…”
Section: Health Problems During Travel and First Arrivalmentioning
confidence: 99%
“…In comparison, such people may be more likely to present at hospital for medically-based treatment, for example, following presentation of physically-based symptoms. Indeed, Pfortmueller et al (2016) found that 43.4%…”
Section: Biomarkersmentioning
confidence: 99%
“…As such, assessment of biomarkers for PTSD by medical staff may not be an unexpected practice and may afford biomedical assessment of correlates of potential trauma-related psychological disturbance present in an individual (Pfortmueller et al, 2016).…”
Section: Biomarkersmentioning
confidence: 99%